L'ivresse du réel : l'objet dans l'art du XXe siècle. - Apollinaire, Guillaume; Baudrillard, Jean; Breton, André; Criqui, Jean-Pierre; De Chirico, Giorgio; Duchamp, Marcel; Foucault, Michel; Lebovici, Elisabeth; Restany, Pierre; Tosatto, Guy (Nîmes : Carré d'Art - Musée d'Art Contemporain de Nîmes, 1993)
Arman ; Armleder, John ; Artschwager, Richard ; Baquié, Richard ; Beuys, Joseph ; Bijl, Guillaume ; Braque, Georges ; Broodthaers, Marcel ; César ; De Chirico, Giorgio ; Cornell, Joseph ; Cragg, Tony (Anthony) ; Dietman, Erik ; Dine, Jim ; Duchamp, Marcel ; Filliou, Robert ; Fritsch, Katarina ; Gnoli, Domenico ; Gober, Robert ; Hains, Raymond ; Johns, Jasper ; Koons, Jeff ; Kosuth, Joseph ; Kounellis, Jannis ; Lavier, Bertrand ; Lichtenstein, Roy ; Magritte, René ; Man Ray ; Merz, Mario ; Oldenburg, Claes ; Pascali, Pino ; Picabia, Francis ; Picasso, Pablo ; Polke, Sigmar ; Rauschenberg, Robert ; Raynaud, Jean Pierre ; Raysse, Martial ; Richter, Gerhard ; de Saint Phalle, Niki ; Schnabel, Julian ; Schwitters, Kurt ; Spoerri, Daniel ; Steinbach, Haim ; Tàpies, Antoni ; Tinguely, Jean ; Tosani, Patrick ; Tremblay, Daniel ; Villeglé, Jacques ; Vilmouth, Jean-Luc ; Warhol, Andy
Frans & Engels
L'ivresse du réel : l'objet dans l'art du XXe siècle, Carré d'Art - Musée d'Art Contemporain de Nîmes, 7 mai - 29 août 1993
boek